2019
DOI: 10.7498/aps.68.20182211
|View full text |Cite
|
Sign up to set email alerts
|

Movement of ablated high-<i>Z</i> plasmas

Abstract: The energy leaking through a slot in the hohlraum filled with low-<i>Z</i> foams is a typical dynamic problem of the ablated high-<i>Z</i> plasmas. In this paper, we develop a simplified one-dimensional model to study the expansion-reverse process of the ablated Au plasmas, which corresponds to the closing-reopening process of a slot. Our work shows that its physical mechanism is the ablation pressure competing with radiation pressure difference and the material pressure of low-<i>… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…The local thermal equilibrium is an important assumption in both Verlinde's entropic gravity [38] and Jacobson's thermodynamic derivation of the Einstein equation [49]. Moreover, it is also a basic assumption in a thin film model (also referred as a membrane model) provided by Zhao and his coworkers [50][51][52] by improving 't Hooft's brick-wall model [53] in order to calculate the statistical entropies of nonstatic black holes or black holes in nonthermal equilibrium. It was found that the local equilibrium near the horizon should be maintained for the black holes with a mass far greater than the Planck scale [48].…”
Section: Stability Of Bec Black Holementioning
confidence: 99%
“…The local thermal equilibrium is an important assumption in both Verlinde's entropic gravity [38] and Jacobson's thermodynamic derivation of the Einstein equation [49]. Moreover, it is also a basic assumption in a thin film model (also referred as a membrane model) provided by Zhao and his coworkers [50][51][52] by improving 't Hooft's brick-wall model [53] in order to calculate the statistical entropies of nonstatic black holes or black holes in nonthermal equilibrium. It was found that the local equilibrium near the horizon should be maintained for the black holes with a mass far greater than the Planck scale [48].…”
Section: Stability Of Bec Black Holementioning
confidence: 99%